Correlation of Estrogen with Serum Insulin and Blood Glucose Levels in Post-menopausal Women (Bangladesh Medical Journal, 2017)
Hyperglycemia is a major risk factor for cardiovascular diseases in postmenopausal women. Increased incidence of cardiovascular diseases in postmenopausal women may be due to hyperglycemia caused by lower level of estrogen hormone. This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka, Bangladesh during the period of January to December 2011 to observe the correlation of estrogen with fasting serum insulin (FSI) and fasting blood glucose (FBG) levels in postmenopausal women. A total of 90 women were selected from different areas of Dhaka city, among them, 60 postmenopausal women of age group 50 to 60 years were taken as study group and 30 apparently healthy premenopausal women of age group 20 to 30 years were included as comparison group. The study parameters fasting blood glucose level was estimated by enzymatic method in both groups. Serum insulin level was estimated by Enzyme Linked Immunosorbent Assay (ELISA) and serum estrogen level by RIA method in order to assess the hormonal level of both groups. Data was analyzed by Unpaired Student’s‘t’ test and Pearson's correlation co-effcient (r) test as applicable. Mean serum fasting insulin level and mean blood glucose level was higher in postmenopausal women than premenopausal and result was statistically significant. In postmenopausal women serum estrogen level was lower than premenopausal and serum estrogen level showed negative correlation with serum fasting insulin level. Blood glucose level also showed negative correlation with serum estrogen level. All these correlation were statistically non-significant. It may be concluded that the serum fasting insulin and blood glucose levels are significantly higher in postmenopausal women that may be due to low level of estrogen.Bangladesh Med J. 2017 Jan; 46 (1): 32-37